Global site-specific N-glycosylation analysis of HIV envelope glycoprotein - Liwei Cao (Nature Portfolio, 2017)
The analysis of site-specific glycosylation of HIV Envelope glycoprotein (Env) is challenging as it contains 25–30 glycosylation sites with multiple glycan forms at each site. Here the authors present a generally applicable mass spectrometry-based method for site-specific analysis of protein glycosylation that they apply to the analysis of the HIV-1 Env.